PENGARUH PERPUTARAN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Food & Beverages yang terdaftar di Bursa Efek Indonesia Tahun 2018-2023): PENGARUH PERPUTARAN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Food & Beverages yang terdaftar di Bursa Efek Indonesia Tahun 2018-2023) - annisa rizky ramadhani siregar; Listiorini; Muhammad Karya Satya Azhar (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to determine the effect of turnover Working Capital and Liquidity on Profitability with Size Company as a moderating variable. This type of research is quantitative research. The population in this study is all Food & Beverages Companies listed on the Stock Exchange Indonesia for the 2018-2023 period. Sampling technique with using a purposive sampling method with a number of samples 28 companies. This research uses data analysis techniques Moderated Regression Analysis (MRA). The results of this research show that Capital Turnover Work has no effect on Profitability. Liquidity has an effect on Profitability. Company size is able to moderate the influence of working capital turnover and liquidity on profitability